2021
DOI: 10.1038/s41467-021-22157-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic synthesis of heterocycles from biomass-derived furfuryl alcohols

Abstract: It is very attractive yet underexplored to synthesize heterocyclic moieties pertaining to biologically active molecules from biomass-based starting compounds. Herein, we report an electrocatalytic Achmatowicz reaction for the synthesis of hydropyranones from furfuryl alcohols, which can be readily produced from biomass-derived and industrially available furfural. Taking advantage of photo-induced polymerization of a bipyridyl ligand, we demonstrate the facile preparation of a heterogenized nickel electrocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 64 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…Having demonstrated, guided by the mechanistic study, that the electrocatalyst can be used as a common platform for the electro‐oxidative oxygenation and dehydrogenation of aliphatic and benzylic alcohols and benzylamine, [ 45 ] we then extended this scope to a more complex reaction, the highly important six‐electron selective oxidation of 5‐(hydroxymethyl)furfural (HMF) to 2,5‐furandicarboxylic acid (FDCA), an essential platform chemical in the polymer industry, ( Figure 7 a). [ 46–49 ] The 1 H NMR peak at ≈4.5 ppm, measured in the starting material, is ascribed to the hydroxymethyl H (H d ). It completely vanishes in the postreaction mixture (Figure 7b, blue), suggesting full conversion of the starting HMF.…”
Section: Resultsmentioning
confidence: 99%
“…Having demonstrated, guided by the mechanistic study, that the electrocatalyst can be used as a common platform for the electro‐oxidative oxygenation and dehydrogenation of aliphatic and benzylic alcohols and benzylamine, [ 45 ] we then extended this scope to a more complex reaction, the highly important six‐electron selective oxidation of 5‐(hydroxymethyl)furfural (HMF) to 2,5‐furandicarboxylic acid (FDCA), an essential platform chemical in the polymer industry, ( Figure 7 a). [ 46–49 ] The 1 H NMR peak at ≈4.5 ppm, measured in the starting material, is ascribed to the hydroxymethyl H (H d ). It completely vanishes in the postreaction mixture (Figure 7b, blue), suggesting full conversion of the starting HMF.…”
Section: Resultsmentioning
confidence: 99%
“…This hybrid water electrolysis demonstrates great potential for H 2 production and electrochemical organic reforming. [312][313][314] Normally, this hybrid water electrolysis technology produces H 2 at the cathode and nongaseous oxidative products. Very recently, Wang et al reported a novel hybrid water electrolyser that combines the cathodic HER and low-potential anodic oxidation of aldehyde with a low onset voltage of merely 0.1 V. 315 Unlike conventional aldehyde electrooxidation at the anode, in which the hydrogen atom of the aldehyde group is oxidized into H 2 O at high potentials and nongaseous product molecules are generated, the lowpotential aldehyde oxidation can produce H 2 from the hydrogen atom of aldehyde at the anode.…”
Section: Hybrid Water Electrolysismentioning
confidence: 99%
“…This problem could be overcomed by employing modified electrodes fabricated with the catalyst which could be highly advantageous in synthesizing a variety of organic molecules. [130][131][132][133][134] These modified electrodes have higher surface area which reduces the current density and avoid the degradation of electrolytes. The fabrication of the catalyst to the electrode makes it advantageous for reusability and easier isolations of the desired product.…”
Section: Electrochemical Metal-free Catalyzed Oxidative Annulationmentioning
confidence: 99%
“…Moreover, the catalyst used in the electrochemical transformations are transition metals, ionic salts, organic hydrazines or organic amines and the use of these catalyst in the solution brings along major disadvantages including difficult isolation and unavoidable side products. This problem could be overcomed by employing modified electrodes fabricated with the catalyst which could be highly advantageous in synthesizing a variety of organic molecules [130–134] . These modified electrodes have higher surface area which reduces the current density and avoid the degradation of electrolytes.…”
Section: Intermolecular and Intramolecular Cyclizationmentioning
confidence: 99%